Pediatric ano-rectal necrosis - Keren Kremer; Dror Mandel; Mark Weinberg; Gad Lotan (Elsevier, 2019)
Anorectal necrosis in children is a rare life-threatening condition whose mention in the literature is sparse. Surgical debridement and protective colostomy have been suggested as approaches for its treatment. One of the major problems associated with anorectal necrosis is necrosis of the rectal mucosa necrosis whose management is difficult.Herein, we present a unique surgical technique that proposes to preserve necrotic mucosa and simultaneously prevent exacerbation of perianal sepsis. Keywords: Anorectal necrosis, Perianal necrosis, Rectal mucosa necrosis